Quand les paroles s’envolent : réflexions sur les caractéristiques et la forme phonétique du High Rising Terminal en anglais contemporain - Stephan Wilhelm (Anglophonia)
The emergence of the so-called High Rising Terminal (HRT) or ‘uptalk’ – that is the use of rising intonation at the end of declarative utterances – is a major contemporary prosodic phenomenon that has been reported in numerous varieties of English worldwide (see for example Lakoff 1975; Ching 1982; Guy & Vonwiller 1984; Guy et al. 1986; Allan 1990; McLemore 1991; Britain 1992a, 1992b; Bradford 1997; Cruttenden 1997; Cheng & Warren 2005; Ladd 1996, 2008; Barry 2007; Liberman 2008; Sullivan 2010).The pragmatic function of the HRT is analysed in many different ways, and there is considerable variation in the descriptions of the speech segments in which it occurs. Besides, some authors (e.g. Hirschberg & Ward 1995, Ladd 1996, Fletcher et al. 2005, Liberman 2006b) insist that the name ‘High Rising Terminal’ implies that the intonation contours favoured by ‘uptalkers’ are mainly high-rises, i.e. rising nuclear tones which start relatively high in the speakers’ pitch range and end at a very high pitch, so that the voice often becomes ‘squeaky’ (Cruttenden 1997). Other research (e.g. Britain 1992, Fletcher & Harrington 2001, Barry 2007), however, suggests that the HRT may differ somewhat from this description.Based on a corpus of personal conversational narratives containing recordings of different geographical varieties of contemporary English, this paper enquires which definitions of the HRT really match the facts and investigates the phonetics of uptalk. It draws a typology of the contours used as phonetic realisations of the High Rising Terminal and identifies some of its peripheral characteristics. The function of the High Rising terminal in conversational narratives is also discussed as well as the syntactic status of the stretches of speech on which it is observed. Observations are derived from the results and applied to the study of the prosody of contemporary English.